THE ROLE OF PARTICIPATORY COMMUNICATION IN COMMUNITY-BASED FOOD SECURITY PROGRAMS: A SYSTEMATIC LITERATURE REVIEW - Windhi Tia Saputra; Ahmad Zaki; Siti Maryam; Rut Rismanta Silalahi (SOSIOEDUKASI, 2026)
This study aims to evaluate the strategic role of participatory communication in strengthening community-based food security programs through a systematic literature review. Adopting the PRISMA 2020 protocol, a search was conducted in the Scopus database for the period 2015-2026 using keyword strings related to participatory communication, stakeholders, and food security. Of the 179 documents initially identified, 114 selected journal articles were analyzed in depth using content analysis techniques. This study finds that, unlike prior reviews that examine participatory communication and collaborative governance as separate strands, this synthesis integrates both perspectives and identifies elite dominance and power asymmetry as the dominant communicative barrier across the reviewed studies. The governance paradigm in the grain production sector has shifted from a one-way technocratic model to a collaborative governance model, positioning farmers and indigenous communities as equal partners. Optimal communication mechanisms such as interpersonal dialogue and public deliberation build a sense of community belonging, while social capital and institutional support catalyze this transition. The study's conclusions emphasize that sustainable food sovereignty can only be achieved through the redistribution of power and the integration of local knowledge into formal policies through emancipatory communication spaces. Policymakers are advised to institutionalize binding co-decision mechanisms in local food governance, rather than relying on consultative-only participatory forums that risk legitimizing predetermined decisions.